Biological Sample Collection to Advance Research and Treatment: A Fight Osteosarcoma Through European Research and Euro Ewing Consortium Statement - Green, Darrell; van Ewijk, Roelof; Tirtei, Elisa; Andreou, Dimosthenis; Baecklund, Fredrik; Baumhoer, Daniel; Bielack, Stefan S; Botchu, Rajesh; Boye, Kjetil; Brennan, Bernadette; Capra, Michael; Cottone, Lucia; et al. (Clinical cancer research, 2024)
Osteosarcoma and Ewing sarcoma are bone tumors mostly diagnosed in children, adolescents, and young adults. Despite multimodal therapy, morbidity is high and survival rates remain low, especially in the metastatic disease setting. Trials investigating targeted therapies and immunotherapies have not been groundbreaking. Better understanding of biological subgroups, the role of the tumor immune microenvironment, factors that promote metastasis, and clinical biomarkers of prognosis and drug response are required to make progress. A prerequisite to achieve desired success is a thorough, systematic, and clinically linked biological analysis of patient samples, but disease rarity and tissue processing challenges such as logistics and infrastructure have contributed to a lack of relevant samples for clinical care and research. There is a need for a Europe-wide framework to be implemented for the adequate and minimal sampling, processing, storage, and analysis of patient samples. Two international panels of scientists, clinicians, and patient and parent advocates have formed the Fight Osteosarcoma Through European Research consortium and the Euro Ewing Consortium. The consortia shared their expertise and institutional practices to formulate new guidelines. We report new reference standards for adequate and minimally required sampling (time points, diagnostic samples, and liquid biopsy tubes), handling, and biobanking to enable advanced biological studies in bone sarcoma. We describe standards for analysis and annotation to drive collaboration and data harmonization with practical, legal, and ethical considerations. This position paper provides comprehensive guidelines that should become the new standards of care that will accelerate scientific progress, promote collaboration, and improve outcomes.
Keywords: Biological Specimen Banks; Bone Neoplasms; Humans; Biomarkers, Tumor; Europe; nádory kostí; Ewingův sarkom; nádorové biomarkery; osteosarkom; Osteosarcoma; Sarcoma, Ewing; odběr biologického vzorku; lidé; Specimen Handling; Evropa; banky biologického materiálu